Partisipasi Masyarakat Dalam Pengembangan Wisata Pantai Cemara Banyuwangi - Ayu Wanda Febrian; Muhamad Ari Perdana (Tourism, Hospitality And Culture Insights Journal, 2023)
Cemara Beach Banyuwangi is a marine tourism object that has great potential to be developed as a tourist destination, both for the domestic and foreign tourism market. The Cemara Beach Banyuwangi area has an attraction as a protected turtle conservation area and the beauty of the beach surrounded by thousands of cypress trees. This study aims to determine the form of community participation in the tourism development of Cemara Beach Banyuwangi. This study uses a qualitative descriptive approach with primary and secondary data sources obtained through observation, documentation, literature review and interview techniques. The results of the study show that the community around Cemara Beach tourism has participated in tourism development through the formation of Community Monitoring Groups (Pokmaswas) / Joint Business Groups (KUB). However, community participation still needs to be increased to optimize the development of tourist areas. Forms of community participation in the development of tourist attractions Cemara Beach Banyuwangi consist of participation in escorting tourism activities, planning, implementing, developing, and evaluating. With increased community participation, it is hoped that the Cemara Beach tourist area can develop more and provide benefits to the surrounding community.